PENGARUH CORPORATE GOVERNANCE DAN KUALITAS AUDITOR TERHADAP MANAJEMEN LABA - Sofyan Effendi; Daljono Daljono (Diponegoro Journal of Accounting, 2013)
Earnings management is the action taken by managers in manipulating financial statements are intended to benefit himself. It is considered as fraud committed by management as detrimental to many parties. This study aims to analyze and provide on empirical evidence of the influence of firm size, board composition, audit committees (audit committee activity and size), ownership (institutional and managerial) and auditor reputation on earnings management.This study used a sample of banking companies listed in Indonesia Stock Exchange (IDX) during the years 2009-2011 with a purposive sampling method and obtained as many as 69 samples. This study uses secondary data from company annual reports obtained from BEI. Data were analyzed using multiple linear regression.The results of this study indicate that the size of the audit committee, managerial ownership and quality auditor significant effect on earnings management. While the size of the company, board composition, audit committee activity and institutional ownership has no significant effect on earnings management.